Integrated pest and disease management for jute and allied fibres - Ramasubramanian, T; Sarkar, S K; Satpathy, S; Laha, S K; De, R K; Gotyal, B S; Biswas, C (Indian Farming, 2015)
Tossa jute is more susceptible to insect pests than white jute with the exception of stem weevil. Yellow mite, semilooper and stem weevil are the major pests of jute. Efforts are on the way to manage the mealy bug (Phenacoccus solenopsis), an emerging threat to jute and mesta. Ramie, sisal and flax are practically free from economic damage of insect pests in India. Endosulfan, carbaryl and cypermethrin are the insecticides recommended for the management of insect pests. Stem rot is an economically important disease of jute. Hooghly wilt was once considered as a major threat to jute crop. After detailed investigation, the CRIJAF has made a recommendation to alter the cropping sequence by incorporating a cereal crop. As a consequence the incidence of the disease has come down to 1-2% or even less. Although resistant varieties are not available at cultivators level, six white jute accessions were identified as resistant genotypes against the most virulent pathotype of Macrophomina phaseolina. Tossa jute ccessions OIN 125, OIN 154, OIN 651 and OIN 853 were categorized as moderately resistant to M. phaseolina after rigorous screening at Sorbhog. Carbendazim, mancozeb and copper oxychloride are in use for the management of diseases of jute and allied fibres. Allied fibre crops are also suffered due to incidence of economically important diseases, bestpet practices are however available to contain the diseases.